(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes innovations in Uzbek poetry by young poets. Under Western influence, young creators are merging their traditions with modern styles, generating new aesthetics. The paper examines how these poets understand and incorporate new themes, techniques, and styles, and the resulting transformations in their work. It also emphasizes how this process contributes to the globalization of Uzbek literature. Insights are offered into young poets’ creative activity and their novel approaches to expressing emotions and social concerns. The article aims to explore the present condition and future direction of Uzbek poetry.